Identification of Novel SARS-CoV-2 Drug Targets by Host MicroRNAs and Transcription Factors Co-regulatory Interaction Network Analysis - Sardar, Rahila; Satish, Deepshikha; Gupta, Dinesh (Frontiers in Genetics, 2020)
Understanding the host regulatory mechanisms opposing virus infection and virulence can provide actionable insights to identify novel therapeutics against SARS-CoV-2. We have used a network biology approach to elucidate the crucial factors involved in host-responses involving host miRNA interactions with host and virus genes using recently published experimentally verified protein-protein interaction data. We were able to identify 311 host genes to be potentially targetable by 2197 human miRNAs. These miRNAs are known to be involved in various biological processes such as T-cell differentiation and activation, virus replication and immune system. Amongst these, the anti-viral activity of 38 miRNAs to target 148 host genes is experimentally validated. Six anti-viral miRNAs, namely, hsa-miR-1-3p, hsa-miR-17-5p, hsa-miR-199a-3p, hsa-miR-429, hsa-miR-15a-5p and hsa-miR-20a-5p, are previously reported to be anti-viral in respiratory diseases and were found to be downregulated. The interaction network of the 2197 human miRNAs and interacting TFs enabled the identification of 51 miRNAs to interact with 77 TFs inducing activation or repression and affecting gene expression of linked genes. Further, from the gene regulatory network analysis, the top 5 hub genes HMOX1, DNMT1, PLAT, GDF1 and ITGB1 are found to be involved in IFN-α2b induction, epigenetic modification and modulation of anti-viral activity. The comparative miRNAs target identification analysis in other respiratory viruses revealed the presence of 98 unique host miRNAs targeting SARS-CoV-2 genome. Our findings identify prioritized key regulatory interactions that include miRNAs and TFs which provide opportunities for the identification of novel drug targets and development of antiviral drugs.